Phylogenetic and morphological resolution of the &ITHelobdella stagnalis&IT species-complex (Annelida: Clitellata: Hirudinea) - Saglam, Naim; Kutschera, Ulrich; Saunders, Ralph; Saidel, William M.; Balombini, Katherine L. W.; Shain, Daniel H. (Magnolia Press, 2018)
The glossiphoniid freshwater leech, Helobdella stagnalis, was described by Linnaeus 1758 based on common European specimens. The presence of a brown, chitinous scute on the dorsal-anterior surface, as observed on leeches elsewhere in the world, has generally led to the classification of all scute-bearing members of the genus as H. stagnalis. Here we describe the morphology and behavior of the type species from Europe, and analyze H. stagnalis-like specimens collected worldwide. We present evidence for at least four distinct scute-bearing Helobdella species that can be morphologically resolved. Maximum Parsimony (MP) and Bayesian Inference (BI) analyses at the mitochondrial cytochrome c oxidase subunit I (COI) locus further supported this notion, with divergence values suggesting a mid-Miocene ancestor of this successful group of cosmopolitan hirudineans. New species, Helobdella echoensis nov. sp., Helobdella eriensis nov. sp., and Helobdella serendipitious nov. sp., are described, based on morphological, anatomical and molecular data. Current distribution patterns of Helobdella spp. suggest a robust, global dispersal mechanism, as well as local pockets of endemism.
Keywords: leech; Hirudinea; scute; COI